2010
DOI: 10.1377/hlthaff.2009.0906
|View full text |Cite
|
Sign up to set email alerts
|

Copayments Did Not Reduce Medicaid Enrollees’ Nonemergency Use Of Emergency Departments

Abstract: Eager to reduce unnecessary use of hospital emergency departments by Medicaid enrollees, states are increasingly implementing cost sharing for nonemergency visits. This paper uses monthly data from the 2001-2006 Medical Expenditure Panel Surveys (MEPS) to examine how changes in nine states' copayment policies influence enrollees' use of emergency departments. The results suggest that requiring copayments for nonemergency visits did not decrease emergency department use by Medicaid enrollees. Future research sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 20 publications
5
36
0
Order By: Relevance
“…3947 The remaining study found a significant relative increase of 34% in ED visits. 48 All studies took place in the United States. The intervention in seven studies was the requirement for patient copayment or coinsurance, and in three it was the implementation of a high deductible.…”
Section: Resultsmentioning
confidence: 99%
“…3947 The remaining study found a significant relative increase of 34% in ED visits. 48 All studies took place in the United States. The intervention in seven studies was the requirement for patient copayment or coinsurance, and in three it was the implementation of a high deductible.…”
Section: Resultsmentioning
confidence: 99%
“…10,34,35 The first difference is a pre-post comparison of hospitals that implement TPR during the study period. The second difference is the experience of rural hospitals that did not participate in the program over the same time period.…”
Section: Methodsmentioning
confidence: 99%
“…48 Three studies were of copayments implemented by state Medicaid programs. [49][50][51] Three of the 5 studies-1 within Kaiser and 2 studies of copayments implemented within the Oregon state Medicaid program-reported significant reductions in ED visits. The Kaiser study found that ED visit rates decreased with increasing copayment levels (adjusted relative rate $1 to $5: 0.962 [95% CI 0.955-0.970] up to $50 to $100: 0.765 [95% CI 0.756-0.774]).…”
mentioning
confidence: 99%